Differential In Vitro Cultivation of Francisella tularensis Influences Live Vaccine Protective Efficacy by Altering the Immune Response - Sunagar, Raju; Kumar, Sudeep; Rosa, Sarah J.; Hazlett, Karsten R. O.; Gosselin, Edmund J. (Frontiers in Immunology, 2018)
Francisella tularensis (Ft) is a biothreat agent for which there is no FDA-approved human vaccine. Currently, there are substantial efforts underway to develop both vaccines and improved tools to assess these vaccines. Ft expresses distinct sets of antigens (Ags) in vivo as compared to those expressed in vitro. Importantly, Ft grown in Brain-Heart Infusion Medium (BHIM) more closely mimics the antigenic profile of macrophage-grown Ft when compared to Muller Hinton Medium (MHM)-grown Ft. Thus, we predicted that when used as a live vaccine BHIM-grown Ft (BHIM-Ft) would provide better protection, as compared to MHM-Ft. We first determined if there was a difference in growth kinetics between BHIM and MHM-Ft. We found that BHIM-Ft exhibited an initial growth advantage ex vivo that manifests as slightly hastened intracellular replication as compared to MHM-Ft. We also observed that BHIM-Ft exhibited an initial growth advantage in vivo represented by rapid bacterial expansion and systemic dissemination associated with a slightly shorter mean survival time of naive animals. Next, using two distinct strains of Ft LVS (WT and sodB), we observed that mice vaccinated with live BHIM-Ft LVS exhibited significantly better protection against Ft SchuS4 respiratory challenge compared to MHM-Ft-immunized mice. This enhanced protection correlated with lower bacterial burden, reduced tissue inflammation, and reduced pro-inflammatory cytokine production late in infection. Splenocytes from BHIM-Ft sodB-immunized mice contained more CD4+, effector, memory T-cells and were more effective at limiting intracellular replication of Ft LVS in vitro. Concurrent with enhanced killing of Ft LVS, BHIM-Ft sodB-immune splenocytes produced significantly higher levels of IFN-γ and IL-17A cytokines than their MHM- Ft sodB immunized counterparts indicating development of a more effective T cell memory response when immunizing mice with BHIM-Ft.